Geomechanical assessment method during the construction of underground by the Hydroelectric Curibamba - Junin - Carlos C., Leoncio (2016)
Fact-finding development of the gallery of prospection for C.H. Curibamba, interpretation and evaluation of the results of a 674,00-meter length, that he understands: Geological mapping, Evaluation geotechnical and Essays in situ, in the cavern of machines of the Project. The development of the works involves in its first phase, geological study - geotechnical detailed in the stretches of excavation of the gallery of prospection: The first stretch that comprises from the progressive 0 +019.20 to 0 +580.00, comprises outburst toward the cavern of machines. The second stretch that comprises from the progressive 0 +580.00 to 0 +674.37, that constitutes the cavern of machines. In the indicated stretches they have come true: Geological evaluation geotechnical, hydrogeology and structural geology. These are the different alternatives of education preliminaries made for the posterior construction of the Central Hydroelectric Curibamba. The geological mapping – geotechnical, has determined through the whole gallery of identified excavation litológica old sieno_granite, they show eight systems of main discontinuities, three systems of faults, three systems of discontinuities with leak of water and other systems of aleatory discontinuities occasionally with presence of water. During the excavation he has crossed over zones of rocks cracking and descostramiento due to pressures of confinement. It has taken effect the evaluation of the quality of the rocky mountain mass using classifications RMR’s geomecánicas of Bieniawski and Barton’s Q with the aim of applying the type of rock and support in this stage of study that is a part of the technical file. During the excavation of the gallery of prospection the rock of class has crossed over II, IAII, IV and V. Being the more predominate the rock of class III. In this first phase came true the essays during the excavation of the gallery of prospection of: Resistance in situ, by means of the photo of data with the hammer of Schmidt, Essay of punctual load and sample taking of rock of the excavation with the aim of evaluating the behavior exposed to wind and weather, made in the laboratory of work, accomplished in all the samples extracted of the gallery of prospection that comprises from the progressive 0 +019.20 to 0 +580.00 (outburst to the cavern) and from the progressive 0 +580.00 to 0 +674.37, (cavern of machines). In the item of findings and recommendations bulges out aspects most important geotechnical, importance of the essays in situ sold off inside the gallery of prospection of the Project Central Hydroelectric Curibamba and your influence of geological study – preliminary geotechnical.